On the rate of convergence of the Ritz method for ordinary differential equations - Yakymiv, R. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We obtain direct and inverse theorems on the approximation of solutions of self-adjoint boundary-value problems for the Sturm-Liouville equation on a finite interval by the Ritz method.